2024
DOI: 10.1029/2023gl106006
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened ENSO Amplitude Contributed to Regime Shift in the Hadley Circulation

Juan Feng,
Shuang Wang,
Jianping Li

Abstract: Understanding the variability in the Hadley circulation (HC) changes is crucial for understanding ocean‐atmosphere interactions. In this study, the variability in the boreal winter HC in the last 4 decades is explored using multiple reanalyzes and model simulations. The results show that regime shift occurred in the leading mode of HC variability. The primary mode of the recent HC is dominated by an equatorially symmetrical pattern, which was considered the second mode in previous studies. The regime shift in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Nevertheless, we found that model experimental results for El Niño (1991, 1994, 1997), La Niña (1998) and neutral (1990, 1993 years are similar (figures not shown). What remains unclear is the relative importance of the two tropical oceans and/or the Indian Ocean on the multi-decadal modulations of this inter-basin connection (Fan & Meng, 2023;Feng et al, 2023Feng et al, , 2024Zhang & Han, 2021;Zhang & Li, 2023). This warrants a thorough investigation in future studies.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Nevertheless, we found that model experimental results for El Niño (1991, 1994, 1997), La Niña (1998) and neutral (1990, 1993 years are similar (figures not shown). What remains unclear is the relative importance of the two tropical oceans and/or the Indian Ocean on the multi-decadal modulations of this inter-basin connection (Fan & Meng, 2023;Feng et al, 2023Feng et al, , 2024Zhang & Han, 2021;Zhang & Li, 2023). This warrants a thorough investigation in future studies.…”
Section: Conclusion and Discussionmentioning
confidence: 97%